Transfusion practices in 12 Neonatal Networks – Are we closer to adopting a restrictive transfusion approach? - Klinger, Gil; Helenius, Kjell; Vento, Maximo; Kusuda, Satoshi; Norman, Mikael; Procianoy, Renato Soibelman; Goswami, Neha; Biran, Valerie; Bassler, Dirk; Reichman, Brian; Skubisz, Aleksandra; Battin, Malcolm; et al. (S. Karger AG, 2026)
Introduction: Recent evidence suggests a restrictive approach toward blood transfusions for management of preterm infants. Objective was to survey blood transfusion practises in preterm neonates <29 weeks' gestation among 12 population-based neonatal networks participating in the International Network for Evaluating Outcomes in Neonates (iNeo).
Methods: An online survey based on 2023 practices was sent to 608 neonatal intensive care units (NICUs): Australia/New Zealand (30), Brazil (20), Canada (32), Finland (5), France (70), Israel (26), Japan (292), Poland (56), Spain (55), Sweden (9), Switzerland (9), and Tuscany, Italy (4). Transfusion thresholds in 4 different scenarios were surveyed: (a) infants invasively ventilated within first 7 postnatal days, (b) infants invasively ventilated after 7 days, (c) stable infants on noninvasive respiratory support, and (d) stable infants requiring no respiratory support.
Results: A total of 382 NICUs (63%) responded. Transfusion practices varied within networks and between countries. For invasively ventilated infants, the transfusion threshold during first 7 days after birth was a hematocrit ≤35% in 79% of NICUs, and at an age ≥8 days, the transfusion threshold was a hematocrit ≤30% in 68% of NICUs. For stable infants on noninvasive ventilation, the transfusion threshold was a hematocrit ≤30% in 80%, and in those without respiratory support, the transfusion threshold was a hematocrit of ≤25% in 68% of NICUs.
Conclusions: Variations exist in blood transfusion practises between countries and within networks. A restrictive transfusion approach based on recent recommendations has been adopted by more than two-thirds of NICUs. Additional research is needed to evaluate whether practices align with intentions and how they impact outcomes.